ANALISIS ASPEK KEUANGAN DAN ASPEK PEMASARAN UNTUK MENILAI KELAYAKAN USAHA PADA UMKM BURGERAK DI KOTA AMBON - Windy; Sitra Yani Belasa; Christina Sososutiksno; Pranatalindo Simanjuntak; Muza Syahraini Prabowo; Nurlina Belasa; Afni Rahman (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study is motivated by the increasing competition of fast food MSMEs in Ambon City, so it is necessary to identify and evaluate the financial conditions and marketing strategies to ensure business sustainability. This study aims to identify and analyze the financial and marketing aspects in determining the feasibility of a business or business in the